Eating disorders in team sports athletes (Research, Society and Development, 2023)
Eating Disorders (ED) encompass a range of psychologically driven syndromes marked by specific and detrimental behavioral patterns, well-documented in clinical history since the Middle Ages. These disorders, primarily affecting young individuals, are characterized by an intense fear of weight gain and active weight loss pursuit, with Anorexia Nervosa (AN) and Bulimia Nervosa (BN) as primary examples. This literature review aims to investigate the prevalence of eating disorders among team sports athletes. A systematic literature review was conducted, utilizing databases including LILACS, SCIELO, VHL, and MEDLINE. Results: The prevalent culture of a lean physique, essential for many sports due to musculoskeletal development requirements, often leads to disparities between an athlete's real and desired body image. This can result in body dissatisfaction. Food deprivation hinders multiple vital physiological functions, including energy production and tissue regeneration, crucial in exercise-related nutrition. Inadequate energy leads to suboptimal performance, fatigue, and potential injuries. Comprehensive care for athletes with eating disorders necessitates both nutritional and psychological support.